2008
DOI: 10.1002/chem.200800716
|View full text |Cite
|
Sign up to set email alerts
|

One‐Electron‐Reduced and ‐Oxidized Stages of Donor‐Substituted 1,1,4,4‐Tetracyanobuta‐1,3‐dienes of Different Molecular Architectures

Abstract: A series of monomeric and oligomeric donor-substituted 1,1,4,4-tetracyanobuta-1,3-dienes (TCBDs) with various topologies have been synthesized by means of thermal [2+2] cycloaddition between tetracyanoethylene (TCNE) and donor-substituted alkynes, followed by retro-electrocyclization. One-electron-reduced and -oxidized stages of the donor-substituted TCBDs were generated by chemical methods. The obtained radical anions and radical cations were studied by using electron paramagnetic resonance/electron nuclear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 51 publications
(44 reference statements)
2
23
0
1
Order By: Relevance
“…The E ox values suggested that the triphenylamine derivatives are stronger donors than the fluorene unit and that the substitution of the methoxy group at the para-position with respect to the nitrogen atom facilitated the oxidation, whereas the cyano group substitution made it more difficult. This result is consistent with the redox behavior of the reported triphenylamine oligomers and polymers without the DPP unit [29][30][31][32][33]. In contrast, the E red values originating from the DPP unit were not affected by the electron-donating comonomer structures.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 91%
“…The E ox values suggested that the triphenylamine derivatives are stronger donors than the fluorene unit and that the substitution of the methoxy group at the para-position with respect to the nitrogen atom facilitated the oxidation, whereas the cyano group substitution made it more difficult. This result is consistent with the redox behavior of the reported triphenylamine oligomers and polymers without the DPP unit [29][30][31][32][33]. In contrast, the E red values originating from the DPP unit were not affected by the electron-donating comonomer structures.…”
Section: Optical and Electrochemical Propertiessupporting
confidence: 91%
“…They were applied as precursors for metallofullerene synthesis [97] or CT-Chromophores [151,152]. In one example a cyanophenyl capped derivative were employed to produce porous MOFs with silver salts [85].…”
Section: Star Compounds With a Benzene Corementioning
confidence: 99%
“…However such structures are apparent as substructures in highly fluorescent materials [99] and CT-chromophores [151,152]. …”
Section: Star Compounds With a Benzene Corementioning
confidence: 99%
“…Recording of their electronic spectra is possible when characteristic absorption bands are intrinsic to radical cations [9]. Magnetic resonance methods are more informative, but their application is limited by short lifetime of radical cation intermediates [10]. Unfortunately, most available methods are almost inapplicable to extremely unstable hydrocarbon σ-radical cations, and only a few examples of such studies have been reported [11].…”
mentioning
confidence: 99%